PELATIHAN DASAR ELECTRICAL HOME APPLIANCE SERVICE SISWA SMK - Maftuhah, Maftuhah; Farahdina, Fijri; Eka Hidayati, Najwa; Rohmah, Rofidatur; Hasanah Firdaus, Zahrotul (ABJIS: Al-Bahjah Journal of Islamic Community Service, 2026)
This Community Service Activity aims to improve teacher competency in compiling and implementing teaching materials for the subjects of Aqidah Akhlak, Prayer Etiquette and Dhikr in class VII MTs Muhammadiyah 17 Kranji. The method used is a participatory and collaborative approach through the stages of needs analysis, planning, mentoring the preparation of learning modules and media, as well as evaluation and reflection with partners. Activity data was obtained through observation, documentation, and reflection, then analyzed descriptively with data reduction techniques, data presentation, and drawing conclusions and validated through source triangulation. The results of the study show that the mentoring of teaching materials has a positive impact on student engagement and understanding, teachers are able to manage classes interactively, and student learning outcomes generally show achievements that exceed the standard of completion. The developed teaching materials strengthen the cognitive, affective, and spiritual dimensions of students and support the role of teachers as facilitators who instill moral values ​​through humanistic learning.